Case Study Of Promacol Steel Industry - Peng, Chan Chon (2009)
This case study is about the development of steel industry over the next decade will have major impacts on firms not only in the steel producing industry but also in the steel consuming segments. These segments include construction, automotive, oil and gas, and mechanical engineering as well as an national economy. It is important for policy makers or top managers to understand the dynamic changes or impacts in this industry and to shape their strategies accordingly.